2007
DOI: 10.1002/cbdv.200790116
|View full text |Cite
|
Sign up to set email alerts
|

The Peptaibol Alamethicin Induces an rRNA‐Cleavage‐Associated Death in Arabidopsis thaliana

Abstract: The plant-metabolic response to amphipathic peptides produced by the soil fungi of the genus Trichoderma remains largely unknown. The present investigation was undertaken to examine the death process in alamethicin-treated Arabidopsis thaliana plantlets. The rapid death triggered by alamethicin (at 50 microM) was shown to be associated with protein-synthesis arrest and with specific cleavage of 18S and 25S ribosomal RNA. The use of an inhibitor of nitric oxide (NO) synthases and of an NO scavenger suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…It has previously been shown that specific cleavage of rRNA occurs among the events that are associated with plantlet death under these conditions. [34] rRNA cleavage was not observed in plants challenged by Alm at lower concentrations. Thus, the death processes that are involved in the A. thaliana defense-like response to Alm at low doses and in the rRNA cleavage-associated death at higher concentrations were associated with different active cellular events.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…It has previously been shown that specific cleavage of rRNA occurs among the events that are associated with plantlet death under these conditions. [34] rRNA cleavage was not observed in plants challenged by Alm at lower concentrations. Thus, the death processes that are involved in the A. thaliana defense-like response to Alm at low doses and in the rRNA cleavage-associated death at higher concentrations were associated with different active cellular events.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, Mel has been shown to be more sensitive than Alm to the proteolytic activity of an Arabidopsis cell extract. [34] The HR-like elicitation and systemic response observed with Alm could be related to a more significant enzymatic stability of the peptaibol in planta due to its high content (37 %) in Aib residues. [42][43][44][45][46][47] The other peptides investigated in this work included the natural peptaibol AmpA, (Leu12-OMe)cervinin, and a set of synthetic lipopeptaibols comprising seven to 19 amino acid residues and bearing a methyl ester at the C terminus and an 1-octanoyl group at the N terminus.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on their results, the authors suggested that a specific stimulus activates RNases which leads to the cleavage of cytosolic and chloroplastic rRNA molecules at specific sites. Experiments conducted with ALM-dUL, a synthetic ALM analogue in which all Aib residues are replaced by leucine moieties, showed that the Aib residues are essential for the induction of rRNA cleavage and triggering plant death [73]. In a subsequent study [74], thaliana increased with the peptaibol's membrane permeabilization ability and was strongly associated with α-aminoisobutyric acid content.…”
Section: Theoretical Studies Zhan and Lazaridismentioning
confidence: 96%